Pengaruh Adanya Chat GPT terhadap Penyelesaian Laporan Praktikum Mahasiswa Program Studi Teknik Informatika di Universitas Muhammadiyah Ponorogo - Balya Fauzia Sya’roni (Modem : Jurnal Informatika dan Sains Teknologi., 2024)
This research aims to analyze the influence of AI Chat GPT in completing practicum reports by students of the Informatics Engineering Study Program at Muhammadiyah University of Ponorogo. The background to this research is based on the increasingly rapid development of AI technology, offering various conveniences in various fields, including education. The aim of the research is to analyze the extent to which Chat GPT influences students' ability to prepare practical reports effectively and efficiently. The research method used is a quantitative method by collecting data through a questionnaire using a Google form which was distributed to active students of the Informatics Engineering study program at Muhammadiyah University of Ponorogo. The results of this research show that Chat GPT significantly increases students' understanding of practical material, helps students solve problems encountered in preparing reports, and reduces the time needed to complete reports. The implication of this research is the importance of integrating AI technology in the learning process to increase student academic effectiveness and efficiency. However, appropriate policies are needed to avoid excessive dependence on this technology.